Pendidikan Politik Bagi Orang Asli Papua Guna Meningkatkan Partisipasi Politik - Fransin Kontu; Ransta Lekatompessy; Dapot Pardamean Saragih; Andri Irawan; Erwin Nugraha Purnama (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to understand and increase the political participation of indigenous Papuans through holistic and sustainable political education. The methods used include surveys, interviews, and participant observation to understand the social, political, and cultural context of indigenous Papuans. Research findings show that obstacles such as lack of access to political information, dominant political culture, and a low understanding of political rights are the main obstacles to their political participation. In response to these findings, a political education approach focused on the empowerment and inclusion of local communities was designed and implemented. This political education programme includes an understanding of political rights, political processes, participation in decision-making, and democratic values. The evaluation results show a significant increase in the political understanding and participation of indigenous Papuans after participating in this political education program. This research contributes to the development of political education strategies oriented towards local communities to increase their political participation and empowerment in the political process in Papua